2011
DOI: 10.1016/j.cell.2011.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Methylation Profiles Reveal Features of Epigenetic Inheritance and Evolution in Primates

Abstract: Summary During germ cell and preimplantation development, mammalian cells undergo nearly complete reprogramming of DNA methylation patterns. We profiled the methylomes of human and chimp sperm as a basis for comparison to methylation patterns of ES cells. While the majority of promoters escape methylation in both ES cells and sperm, the corresponding hypomethylated regions show substantial structural differences. Repeat elements are heavily methylated in both germ and somatic cells; however, retrotransposons f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
379
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 361 publications
(425 citation statements)
references
References 64 publications
44
379
2
Order By: Relevance
“…We computed the methylation level in sperm at each of the identified AMRs using data from a previous study (31). Among the 579 autosomal AMRs common to three out of five uncultured methylomes, 146 were methylated (>50%) in sperm.…”
Section: Genome-wide Amr Identification Predicts Imprinted Genesmentioning
confidence: 99%
“…We computed the methylation level in sperm at each of the identified AMRs using data from a previous study (31). Among the 579 autosomal AMRs common to three out of five uncultured methylomes, 146 were methylated (>50%) in sperm.…”
Section: Genome-wide Amr Identification Predicts Imprinted Genesmentioning
confidence: 99%
“…Twenty-one significant clusters of these CpG 'beacons' were determined by permutation and these loci were enriched for neurological disease due to co-location with monogenic neurological and developmental disorders. CpG 'beacons' individually were enriched within SVA repeats, the class that is enriched for sperm hypomethylation from Molaro et al [93]. Furthermore, using primate comparative DNA methylome data, CpG density gain indicated by CpG 'beacons' correlated with reduced methylation in orthologous CGIs in these species over evolutionary time.…”
Section: Clustering Of Species-specific Cpgsmentioning
confidence: 81%
“…Molaro et al investigated the sperm DNA methylome by BiS-seq between human and chimpanzee, and identified extended hypomethylation around CGI regions in comparison to embryonic stem cells, analogous to CGI shore regions [93]. A subsequent tidal reduction in size of these hypomethylated regions was observed with differentiation.…”
Section: Germline Influences On the Evolution Of Dna Methylationmentioning
confidence: 99%
“…A correct pattern of DNA methylation is a requirement for fertility, embryo development and viability of the offspring (O'Doherty and McGettigan 2014;Jenkins and Carrell 2012b;Jenkins and Carrell 2012a). With the description of the human sperm methylome, a methylation status at 70 % of genomic CpGs has been considered as "normal" in human sperm (Molaro et al 2011), lower to that observed in zebrafish, with 95% of methylated CpGs (Potok et al 2013). Sperm DNA methylation pattern is close to that observed in embryonic stem cells, showing hypomethylation at developmental promoters (Hammoud et al 2009;Schagdarsurengin et al 2012).…”
Section: The Importance Of Chromatin Methylationmentioning
confidence: 99%